Civil Law Review of The Implementation of Franchise Agreements In Indonesia - Vitranilla, Yudith Evametha (CV. Publikasi Indonesia, 2024)
Franchise agreements have become one of the fastest-growing business models in Indonesia. However, in its implementation, legal problems often arise faced by the parties involved in the franchise agreement. This journal aims to review the implementation of franchise agreements in Indonesia from the perspective of civil law. This review was carried out by analyzing laws and regulations related to franchising, principles of civil law, and the practice of implementing franchise agreements in the field. The study results show that implementing franchise agreements in Indonesia still faces several obstacles, such as: 1) Lack of understanding of the parties to their rights and obligations in the franchise agreement. 2) Weak law enforcement against violations of franchise agreements. 3) The government's role in protecting the parties' rights in the franchise agreement has not been optimal. Based on the study's results, this journal recommends several steps to improve the implementation of franchise agreements in Indonesia: Increasing education and socialization of the parties about their rights and obligations in franchise agreements; Strengthening law enforcement against violations of franchise agreements; and Enhancing the role of the government in protecting the rights of the parties to the franchise agreement.